Apatite and zircon fission-track data summary (Table S3) - Falkowski, Sarah; Ehlers, Todd A (In: Falkowski, S; Ehlers, TA (2023): Low-temperature thermochronometric data (AHe, AFT, ZHe, ZFT) from three bedrock sample transects across the eastern Central Andes, southern Peru [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.955437, 2023)
This dataset summarizes the apatite fission-track (AFT) data for 24 samples and zircon fission-track (ZFT) data for 11 samples. Single-grain data for AFT and ZFT are presented in Table S4 and Table S5, respectively. AFT and ZFT data were acquired between 2020 and 2021 using the external detector and zeta-calibration techniques at the University of Tübingen, Germany.
Keywords: apatite fission-track thermochronology; Apatite (U-Th)/He thermochronology; Central Andes; erosion; exhumation; low-temperature thermochronology; South Peru; zircon fission-track thermochronology; zircon (U-Th)/He thermochronology